Temporal and Quantitative Analysis of Aortic Immunopathologies in Elastase-Induced Mouse Abdominal Aortic Aneurysms. (16th November 2021) - Tian, Kangli; Xia, Congcong; Liu, Haole; Xu, Boyu; Wei, Panpan; Fu, Weilai; Lu, Ming; Li, Yankui; Li, Yafeng; Cheng, Daxin; Liu, Enqi; Zhao, Sihai
Abstract : Objective . Elastase-induced abdominal aortic aneurysm (AAA) model is widely used for aneurysmal pathogenesis and translational research. However, temporal alternations in aneurysmal histologies remain unknown. This study is aimed at analyzing temporal immunopathologies of aneurysmal aorta following experimental AAA induction. Methods . Male C57BL/6J mice at the age of 10-14 weeks received intra-aortic infusion of elastase to induce AAAs. Aortic diameters at the baseline and indicated days after AAA induction were measured, and aortae were collected for histopathological analysis. Results . Aorta diameters increased from 0.52 mm at the baseline levels to 0.99 mm, 1.34 mm, and 1.41 mm at days 7, 14, and 28, respectively, corresponding 90%, 158%, and 171% increases over the baseline level. Average aortic diameters did not differ between days 14 and 28. Severe elastin degradation and smooth muscle cell depletion were found at days 14 and 28 as compared to the baseline and day 7. No difference in the scores of medial elastin and SMC destruction was noted between days 14 and 28. Consistent results were found for leukocyte accumulation, neoangiogenesis, and matrix metalloproteinase expression. Twenty-eight days after AAA induction, all aneurysmal pathologies showed an attenuated trend, although most histopathological parameters did no differ between days 14 and 28. Conclusion . Our data suggest that almost aneurysmal immunohistopathologies reach maximal 14 days following AAA induction. Analysis of day 14 histologies is sufficient for AAA pathogenesis and translational studies in elastase-induced mouse experimental AAAs.